Comparative analysis of basal locomotor activity-related metabolic phenotypes between C57BL/6 mice and ICR mice substrains derived from three different sources - Hwang, Dong-Ju (Lab Anim Res, 2017)
Animal model, as an indispensable tool for scientific purposes of biomedical researches and clinical application, is a commonly used in various researches. Regarding to this, it is necessary to establish the metabolic phenotype of animal model to minimize spurious interpretations and ensure a level of accuracy and reliability adequate for experimental research. However, the metabolic phenotype-related analysis within rodent strains derived from different source is nonexistent, especially in C57BL/6Korl mice and Korl:ICR mice (a domestic mouse strain). To compare the physiological and metabolic phenotypes over a period of time, we utilized the C57BL/6 mice (C57BL/6Korl, A:C57BL/6, and B:C57BL/6) and ICR mice (Korl:ICR, A:ICR, and B:ICR) derived from three different sources. Our data showed that average body weight, body temperature, food intake, and water consumption have a similar tendency among the C57BL/6 and ICR groups, except for the higher body weight of C57BL/6Korl mice over a period of time. Moreover, some significant differences was observed in adipose tissue mass and adipocyte size among the groups, with a higher tendency of C57BL/6Korl mice and Korl:ICR mice. Most importantly, resting metabolic rate (RMR) serves as an approximation of the metabolic phenotype showed no significant difference among the groups of C57BL/6 mice and ICR mice, except for the lower oxygen uptake of C57BL/6Korl mice compare to the A:C57BL/6 mice. Taken together, our data suggest that C57BL/6 mice and ICR mice derived from three different sources have an overall similar feature of physiological and metabolic phenotypes.